Inovasi Media Flipbook Berbasis Problem Based Learning Pada Materi Ekosistem Untuk Siswa Sekolah Dasar - Desi Minatanti Dwi Pratiwi; Rahyu Setiani; Ajar Dirgantoro (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to develop flipbook learning media based on Problem Based Learning (PBL) in the subject of Science on ecosystem material for fifth grade elementary school students to increase student motivation and learning activity. The research method used is Research and Development (R&D) with the Borg and Gall model. Data collection techniques include observation, interviews, and questionnaires, with 37 students of Elementary School Cluster 3, Bandung District as research subjects. The validation results show that the media is categorized as very valid, with a score from material experts of 99.77% and media experts of 99.09%. The practicality of the media is shown from teacher observations with an average score of 94.64% (limited classes) and 92.85% (large classes), which are categorized as very practical. The effectiveness of the media is proven by the increase in learning outcomes through an average n-Gain of 0.76 (limited classes) and 0.804 (large classes), both in the high category. The results of the paired t-test show a significant difference between the pretest and posttest with a significance value of <0.001. Student responses to the media were also very positive, with an average of 94.28% (small class) and 95.71% (large class). Thus, this PBL-based flipbook proved valid, practical, and effective in improving student learning outcomes. The contribution of this research lies in providing an alternative interactive digital media based on PBL that can be integrated into science learning to encourage active student engagement and meaningful learning.